Indicadores educacionais de desenvolvimento profissional da docência em música nos anos finais do ensino fundamental - Machado, Daniela Dotto (2014)
This dissertation aims at investigating educational indicators of professional development in teaching through the participation of novice and experienced music teachers in the late years of elementary school in a continuing education distance program. The study is based on the notions of educational indicators and educational indicators of professional development in teaching proposed by Reali (2009) and Reali et al. (2004), in Shulman s theory on teachers professional knowledge base and the pedagogical reasoning process (1986; 1987; 2005) as well as on teachers professional experience based on Tardif (2012). In this qualitative study, the constructive-collaborative method of intervention-research was used, in which the teachers narratives concerning their education and professional practice were considered. Music teachers continuing distance education was developed from April to December 2011 on the UFSCar Teachers Portal. Tools of software packages Moodle and Skype were used for data collection in the study. After completing the program, thirteen (13) music teachers in the late years of elementary school were selected and constituted the study sample. In its results, the investigation found eleven (11) educational indicators of professional development in music teaching. As regards novice teachers, it was observed that they tend to not master all the necessary knowledge for teaching; show greater difficulties in planning activities and defining contents to be taught; tend to master and use some technologies applied to musical reproduction and practice in music teaching. Concerning the experienced teachers, it was observed that, in atypical situations of professional practice, they show difficulties in mastering music content, in choosing contents to be taught and in planning lessons; are concerned about getting to know students and their involvement with music better; seek for information on songs of students interest, even if their treatment does not exclusively take place in class; show to be more secure in defining the music contents to be taught; are concerned about students broader development and not only about their learning music content; show to have greater access to and greater knowledge of music teaching materials; tend to show tranquility when coping with situations that arise unexpectedly; and are constantly learning.